"SILVER LEGENDS" IN TAIWAN - AN APPLICATION FROM LIFE REVIEW TO PRODUCTIVE AGING. (11th November 2018) - Kuo, T
Abstract: Life review often led to better understanding of self and leading to life integration or self-actualization. The purpose of this research was to examine what characteristics existed when 15 older adults participated in a 10-session life review group, with the objective to share their life stories to different audiences upon the completion of the group. The 15 older adults were called "Silver Legends." Both the life review content and interviews after sharing in the communities were analyzed qualitatively by using content analysis. This results were 10 characteristics organized into three categories: charisma, preservation and contribution. The 10 characteristics were persistence, positive attitudes, interests, self-concept, learning, creativity, flexibility and replacement, passing down skills, participation and sharing and having plans. This study concluded by discussing that the effect of life review groups allowed older adults to stay productive by further developing their life potentials and making contributions in the society.